2017
DOI: 10.3126/jcmc.v6i1.16655
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of family planning among married women of reproductive age in a VDC of eastern Nepal

Abstract: Contraceptive use and fertility rates vary substantially among developing countries. An important factor, which affects the fertility of any population, is Contraceptive .Contraceptive use varies by age. Nepal over the past 15 years show an impressive increase in the use of modern contraceptive methods from 26 percent in 1996 to 43 percent in 2011.Objectives of the is to assess the knowledge, attitude regarding family planning and the practice of contraceptives among the married women of Dhabi VDC of Eastern N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 2 publications
6
12
0
Order By: Relevance
“…Most of them(83.3%) were Hindu by religion and 23.7% of respondents were illiterate. 7 These findings were consistent with the present study result except mean age of respondents. The mean age of respondents was higher in present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Most of them(83.3%) were Hindu by religion and 23.7% of respondents were illiterate. 7 These findings were consistent with the present study result except mean age of respondents. The mean age of respondents was higher in present study.…”
Section: Discussionsupporting
confidence: 93%
“…The present study found that 60.8% respondents were currently using family planning methods which is consistent with finding of NDHS 2016 (53%), 3 Lindstorm (48%), 5 Uprety (63.6%), 7 Gupta (68%), 9 andDabral (61.6%). 10 The present study found that 26.7% of the respondents were using Depo Provera followed by IUCD (2%), pills (2%), and 12.7% had undergone female sterilization.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…United Nations millennium development goal (MDG) 2015 report for African continent (33.4%) [2], and the 2015 sub-Saharan MDG reports [2]. 2016 Ethiopian DHS for Amhara region, 46.9% [9], Gondar, Nekemte [21], Debreberhan [15], and west Gojjam [22], Ghana [22,23], Kenya [2] and Nepal [24]. The United Nations MDG 2015 report for Somalia, Eritrea, and South Sudan which was 23.7, 20 and 6.8% respectively [2].…”
Section: Discussionmentioning
confidence: 99%
“…This is also similar with other findings [ 18 , 22 , 26 ]. The reason might be due to the fact that women with no formal education have deprived autonomy to make decisions on reproductive health issues including when to use contraceptives [ 29 ].…”
Section: Discussionmentioning
confidence: 99%